FEATURES OF GENE POLYMORPHISMS OF IL-6 (IL-6-174G/C IL-6-572G/C) IN PATIENTS OF DIFFERENT ETHNIC GROUPS WITH CORONARY HEART DISEASE (LITERATURE REVIEW) - Olga Valentinovna Smirnova; Vitaly Sergeevich Kablukov (В мире научных открытий, 2018)
The aim of the study: to Provide the reader with a detailed overview of the features of IL-6 gene polymorphism in patients of different ethnic groups with coronary heart disease (CHD), as well as to investigate the effect of different genotypes of single-nucleotide polymorphisms of interleukin IL-6 on the circulation levels of inflammatory and anti-inflammatory cytokines in patients with different frequencies of alleles with CHD.